Pengaruh Greed, Opportunity, Need, Exposure Terhadap Perilaku Kecurangan Akademik Pada Mahasiswa Akuntansi Program S1 Negeri Di Bali - ., Gusti Ayu Putu Sri Indrawati; ., I Gusti Ayu Purnamawati, S.E.; ., Anantawikrama Tungga Atmadja,SE,Ak.,M. (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bertujuan untuk mengetahui pengaruh Greed, Opportunity, Need Dan Exposure terhadap perilaku kecurangan akademik pada mahasiswa Akuntansi S1 Negeri Di Bali. Jenis penelitian ini merupakan penelitian kuantitatif, dengan menggunakan kuesioner sebagai instrumen penelitian. Teknik sampel yang digunakan yaitu incidental sampling dimana responden yang dijumpai oleh peneliti secara proposional. Penelitian ini menggunakan 150 responden. Data yang digunakan dalam penelitian ini adalah data primer. Data diperoleh berupa jawaban dari responden di tabulasi dan diolah dengan menggunakan software SPSS versi 16. Hasil penelitian ini menyatakan bahwa Greed, Opportunity, Need Dan Exposure secara parsial berpengaruh signifikan terhadap perilaku kecurangan akademik pada mahasiswa Akuntansi S1 pada di Universitas Negeri Di Bali.Kata Kunci : Greed, Opportunity, Need Dan Exposure, perilaku kecurangan akademik This study aims at determine the effect of Greed, Opportunity, Need and Exposure to the behavior of academic cheating on S1 Accounting students at the State University in Bali. This research type was quantitative research, by using questioner as the research instrument. The sample technique used was incidental sampling, in which the respondents encountered by researchers proportionally. This study employed 150 respondents. The data used in this study were the primary data. . The data obtained were in the form of answers from the respondents, tabulated and processed through SPSS software version 16.The results of this study stated that Greed, Opportunity, Need And Exposure partially significant effect on the behavior of academic cheating in S1 Accounting students at the State University In Bali.keyword : This study aims at determine the effect of Greed, Opportunity, Need and Exposure to the behavior of academic cheating on S1 Accounting students at the State University in Bali. This research type was quantitative research, by using questioner as the research instrument. The sample technique used was incidental sampling, in which the respondents encountered by researchers proportionally. This study employed 150 respondents. The data used in this study were the primary data. . The data obtained were in the form of answers from the respondents, tabulated and processed through SPSS software version 16.The results of this study stated that Greed, Opportunity, Need And Exposure partially significant effect on the behavior of academic cheating in S1 Accounting students at the State University In Bali.